Enoviti magistrski študij na Medicinski fakulteti v Ljubljani - Švab, Igor (Zdravniški vestnik, 2012)
In the academic year 2009/2010 the Faculty of Medicine in Ljubljana launched anew curriculum in medicine and dental medicine. It consists of a unified mastersć programme, prepared along the lines of the Bologna process. Its aims include continuous learning, integration of subjects, unification of the teaching process, introduction of electives, active role of students, implementation of more modern teaching methods and contact with patients and practice already from the beginning of the study. The article describes the process of implementation, main characteristics of the curriculum and first experiences. The first results show that the changes were successful. Nevertheless, the authors point out that the curriculum reform is a long-term process that is not limited only to the modifications of the timetable, but influences a range of other activities of the medical faculty.
Keywords: Education, Medical, Graduate; Educational Measurement; Faculty, Medical; Fakulteta medicinska; Izobraževanje medicinsko, podiplomsko; Izobraževanje, merjenje uspehov; Organization And Administration